TEACHING WRITING SKILLS (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2025)
The article  under discussion depicts the significance of communicative competence in the teaching of writing skills. It aims to analyze the role of effective communication in enhancing students' writing abilities and to propose strategies and methodologies that can be employed by teachers to develop communicative competence in their writing instruction. The article  focuses on understanding the components of communicative competence, investigating its impact on writing proficiency, and examining practical approaches to incorporate communicative competence in the classroom.